IJCM_22A: Impact of Pranayama and Dhyana intervention on metabolic syndrome among women: community based repeated measures design - Rao Chythra R; Bidnurmath Ashwini S; Shetty Avinash; Kamath Asha (Wolters Kluwer Medknow Publications, 2024)
Background: Prevalence of metabolic syndrome among adults in India, is reported to be around 20%-25%, with significantly higher proportion among women than men. Yoga interventions has been promoted as an important non- pharmacological tool to address the growing burden of non-communicable diseases. Objectives: To assess the effectiveness of a pranayama and intervention (yoga) intervention on various components of metabolic syndrome among 30 to 60-year-old women with hypertension. Methodology: A community based repeated measures design was undertaken 156 among hypertensive women (79 intervention, 77 controls) residing in coastal part of southern India. Anthropometric measurements, blood pressure, fasting blood glucose (FBS) and lipids were measured. Six-month pranayama and dhyana intervention were administered to the intervention arm, whereas routine treatment was continued for the control arm. Follow-up was done to ensure practice of interventions while investigations were done at baseline and 6th month. Results: Majority of the women in the intervention and control arm were aged 45-60 years. In the intervention arm, using the National Cholesterol Education Program (NCEP) Adult Treatment Panel III (ATP III) criteria, most [57(72.2%)] of the women had elevated blood pressure. Nearly half of them [38(48.1%)] had abdominal obesity, elevated FBS was seen among 39(49.4%) and 50.6% had low HDL. Hypertriglyceridemia was seen in less than a third [23(29.1%)] women. In the control arm, most [52(70.3%)] of the women had elevated blood pressure, 27(36.5%)] had abdominal obesity, half of them had elevated FBS [39(52.7%)] and low HDL [36(48.6%)]. Hypertriglyceridemia was seen in 21(28.4%) women. No significant change was noted at the end of 6th month follow-up in body mass index (BMI) (p=0.533), systolic(p=0.051) and diastolic blood pressure (p=0.485). Conclusion: There was no significant difference in the 6th month prevalence of components of metabolic syndrome compared to baseline, in both arms of the study.